1996
DOI: 10.1007/bf02088556
|View full text |Cite
|
Sign up to set email alerts
|

Blood leukocyte differential inHelicobacter pylori infection

Abstract: Helicobacter pylori causes a chronic infection in gastric mucosa, but its systemic effects are largely unknown. Our aim was to characterize the effect of H. pylori infection and gastric mucosal inflammation on the peripheral blood leukocyte count. An endoscopic series of 96 patients (40 men and 56 women), with a mean age of 62 years (range 49-80) was studied. Endoscopy with eight stepwise biopsies was performed and the occurrence of H. pylori was studied from sections stained with Warthin-Starry. The severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 21 publications
4
29
2
Order By: Relevance
“…These findings indicate that H. pylori colonization of the gerbil stomach leads to not only a gastric mucosal inflammatory response but also a systemic response. Previous studies reported that humans infected with H. pylori have significantly higher leukocyte counts than their uninfected counterparts (62,63). The leukocytosis observed in H. pylori-infected gerbils in the current study was substantially greater than the leukocytosis previously observed in H. pylori-infected humans.…”
Section: Discussioncontrasting
confidence: 71%
“…These findings indicate that H. pylori colonization of the gerbil stomach leads to not only a gastric mucosal inflammatory response but also a systemic response. Previous studies reported that humans infected with H. pylori have significantly higher leukocyte counts than their uninfected counterparts (62,63). The leukocytosis observed in H. pylori-infected gerbils in the current study was substantially greater than the leukocytosis previously observed in H. pylori-infected humans.…”
Section: Discussioncontrasting
confidence: 71%
“…There is compelling evidence that basophils and their mediators participate in host defense against parasites (79) and viruses (24,31,32,64). It has been shown that peripheral blood basophils may be increased in H. pylori-positive patients (36). In this study, we provide the first direct evidence that basophils can contribute to H. pylori-induced mucosal inflammation and that a bacterial infection is associated with basophil infiltration.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, H. pylori is involved in mast cell chemotaxis, and activation and release of proinflammatory mediators and cytokines. Although peripheral blood basophils may be increased in H. pylori-positive patients (36), studies of the in vitro effects of H. pylori on histamine release from basophils have yielded inconclusive results (37)(38)(39).…”
mentioning
confidence: 99%
“…Hence, Ig-producing cells should be taken into consideration in the estimation of H. pylori -associated gastric inflammation. Higher peripheral blood leukocyte count [152] and serum levels of anti- H. pylori [153, 154] have also been reported to be associated with increased grading of inflammation, although studies on these factors are limited.…”
Section: Immunoglobulin Production and Othersmentioning
confidence: 99%